Preparation and characterization of pure natural hydroxyapatite derived from seashells for controlled drug delivery - OKTAR, FAİK NÜZHET; GÜNDÜZ, OĞUZHAN; BİLĞİÇ ALKAYA, DİLEK; AYAZ SEYHAN, SERAP; CESUR, SÜMEYYE (My University, 2022)
The marine species are specially used for the fabrication of bioceramic nano-powders with natural methods for their use in controlled drug delivery. However, there are only very limited studies regarding the production and synthesis of hydroxyapatite (HA)-based drug delivery systems from marine structures. In this study, poly (vinyl alcohol) (PVA) containing Rifampicin (RIF)-loaded Orange Spiny Oyster Seashell (Spondylus barbatus) hydroxyapatite (HA) composite is synthesized by an in situ ultrasound-assisted method. All samples were analyzed by X-ray diffraction (XRD), Fourier transforms infrared (FTIR) spectroscopy, and Scanning electron microscope (SEM), respectively. The in vitro drug release tests of the obtained samples were performed in a phosphate-buffered medium (PBS) at 37 degrees C. Drug release was evaluated according to five varying kinetic models. In vitro RIF release from HA/PVA composite in phosphate buffer (pH 7.4) showed prolonged sustained drug release. From the drug release kinetic models, Higuchi and Korsmeyer-Peppas were found to be the best model for the three ratios based on the correlation coefficient. The diffusion component is less than 0.5, which indicates quasi-fickian diffusion. From the kinetic study results, the RIF-loaded marine phase composite has potential use in drug delivery applications as it shows positive sustained drug release behavior.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; MALZEME BİLİMİ, SERAMİK; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MATERIALS SCIENCE, CERAMICS; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); Genel Malzeme Bilimi; Seramik ve Kompozitler; Fizik Bilimleri; General Materials Science; Ceramics and Composites; Physical Sciences; Hydroxyapatite; Poly (vinyl alcohol); Rifampicin; Polycomposite; Drug delivery; Kinetic model; CERAMIC COMPOSITES; IN-VITRO; RELEASE; SCAFFOLDS; POWDERS; Hydroxyapatite; Poly (vinyl alcohol); Rifampicin; Polycomposite; Drug delivery; Kinetic model